Pendekatan Dakwah Komunitas Majelis Zikir Al-Hidayah Bengkalis dalam Penguatan Spiritualitas dan Solidaritas Sosial Masyarakat Melayu - Amrizal Amrizal; Prayugo Prayugo; Ramos Sari (Program Studi Manajemen Dakwah Fakultas Ushuluddin Dan Dakwah Uin Raden Mas Said Surakarta, 2026)
This study aims to explore the community da’wa approach of the Majelis Zikir al-Hidayah Bengkalis using qualitative methods with a case study approach. Data sources were obtained from observations of activities and interviews with the Majelis leaders. The results of the study show that the community-based da'wah approach applied by the Bengkalis Al-Hidayah Zikir Council consists of ritual-spiritual, emotional and symbolic, educational, relational, therapeutic, and social approaches. This approach has a significant impact on strengthening the spirituality of the congregation, their psychological and emotional condition, social bonds and solidarity, behavior and morals, intellectual and religious awareness, and institutional existence and loyalty. On the other hand, the challenge that still exists is that the religious study material still seems simple and not comprehensive due to the limited knowledge of the Majelis leaders in Islamic disciplines. This study recommends the importance of involving Muslim intellectual figures from external circles to fill in broader and more in-depth Islamic studies. This study provides theoretical and practical contributions to the development of relevant and impactful community-based da'wah strategies.